IMPLEMENTATION OF COACHING FOR ROOM HEAD TOWARDS IMPROVING CARING BEHAVIOR: LITERATURE REVIEW - Prawira, Ricky; Saputra, Dikki (School of Nursing, Faculty of Medicine, Tanjungpura University, 2025)
Background: Nursing services are part of health services in hospitals and have great leverage in achieving hospital goals, nursing services are closely related to caring attitudes, this attitude should be maintained and supervised by a manager or head of the room. The implementation of coaching is a strategy that can be adopted to ensure that nurse caring continues to run well. The literature review method is by selecting articles published in 2018-2024 in five databases, namely ProQuest, Science direct, Pubmed, JSTOR and Springer-Link. Based on the search, eight articles were analyzed and the results showed that coaching the head of the room on the level of caring for nurses. There are 5 articles (n = 5) that conduct research related to caring for patients, and there are 3 articles (n = 3) research articles that discuss caring for the work environment. The implementation of coaching the head of the room has been proven to have benefits in the field of nursing, especially for nurses in hospitals. Coaching needs to be developed in the Hospital through support from Hospital management by making policies and as a solution to achieve the goals of the hospital. Keywords: Caring, Coaching, Leadership Nursing.